Stress in small town and rural law enforcement: Testing the assumptions - Oliver, Willard M. (American journal of criminal justice, 2004)
Sandy and Devine (1978) theorized that small-town and rural police officers experienced Stressors different from their urban counterparts. They delineated four rural stress dimensions: security, social factors, working conditions, and inactivity. Despite the number of hypotheses annunciated by these authors from their exposure to small-town and rural police, they have never been tested. This study is an attempt to rectify this deficiency in the literature by testing their theory/hypotheses with data derived from a survey questionnaire of West Virginia law enforcement officers. The findings of this study lend support for many of the original hypotheses and all four of the dimensions.